Early and late Holocene paleoenvironmental reconstruction of the Pearl River estuary, South China Sea using foraminiferal assemblages and stable carbon isotopes - Chen, Huixian (2020)
Proxy reconstructions of estuarine evolution provide perspectives on regional to global environmental changes, including relative sea-level changes, climatic changes, and agricultural developments. Here, we present a new benthic foraminiferal record along with δ13C and C/N, and lithological data from a sediment core in the Pearl River estuary (Lingding Bay) adjacent to the South China Sea. The core has relatively thick Holocene sediments (>40 m) due to its location in the paleo-valley of the Pearl River. The lithologic and foraminiferal record reveal an evolution in paleoenvironment from fluvial, inner estuary to middle estuary between 11300 and 8100 cal a BP in response to rapid sea-level rise. δ13C and C/N data indicate high freshwater discharge from 10500 to 8100 cal a BP driven by a strong Asian monsoon. The middle Holocene (8100 - 3300 cal a BP) sediment is absent in the core due to subaqueous erosion resulting from the unique geomorphology of the Pearl River Delta. In the late Holocene from 3300 cal a BP to the present, the lithology and foraminiferal assemblages suggest a further evolution from outer estuary, middle estuary channel, to middle estuary shoal, resulting from deltaic progradation under stable relative sea levels. In the last 2000 years, δ13C and C/N values reveal the intensive development of agriculture coupled with the reduction of freshwater input derived from a weakening Asian monsoon.